International criminal law and sexual violence against women : the interpretation of gender in the contemporary international criminal trial - Nadj, Daniela (Routledge research in international law., 2018)
Focusing on the International Criminal Tribunal for the Former Yugoslavia and the International Criminal Tribunal for Rwanda as well as subsequent developments in the International Criminal Court, the book shows how the tribunals have delivered landmark jurisprudence in the area of sexual violence against women and provided a legacy for how gender justice is incorporated into international law. However, Daniela Nadj argues that in the relevant cases there is a tendency to depict women in monolithic fashion with little agency or sense of identity beyond their ethnicity. By bringing to the surface the complexity and multi-faceted gendered identities in wartime, the book calls for a reconceptualisation of notions of femininity in armed conflict.